METAPHORICAL MODELING IN SPANISH SLANG: FROM COGNITIVE STRUCTURES TO LINGUISTIC REALIZATIONS - Abdullaev Marks Kamilzhanovich (Western European Studies, 2025)
This study investigates cognitive mechanisms underlying metaphorical processes in Spanish slang through conceptual metaphor theory. Drawing on Lakoff and Johnson’s framework, this research examines how abstract concepts in colloquial Spanish are systematically structured through metaphorical mappings from concrete experiential domains. The analysis reveals that Spanish slang demonstrates rich metaphorical productivity across several source domains, including anthropomorphic conceptualizations, zoomorphic projections, spatial orientations, and gastronomic metaphors reflecting cultural-linguistic patterns. Through corpus analysis of contemporary Spanish slang expressions, this study identifies recurrent metaphorical models demonstrating how embodied cognition principles manifest in informal language varieties. The findings indicate that metaphorical modeling serves multiple pragmatic functions including expressiveness, euphemism, group identification, and creative language play, while revealing culture-specific patterns that distinguish Spanish from other languages
Keywords: conceptual metaphor; Spanish slang; cognitive linguistics